2018
DOI: 10.1021/acssuschemeng.8b05364
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Inherent Minerals with Carbon during Biomass Pyrolysis Weakens Biochar Carbon Sequestration Potential

Abstract: Biomass carbon could be sequestrated in form of biochar, an aromatized carbon structure produced by pyrolysis. Inherent minerals are reactive constituents that interact with organic contents during pyrolysis, significantly affecting the properties of the pyrolysis product. Despite their importance, their influence on biochar-carbon sequestration has been rarely studied. This study selected four types of biomass: barley grass, peanut hull, cow manure and sewage sludge to investigate the influence of inherent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…To efficiently recover P from P extract, pretreatment of SS is necessary to produce SSB with a high P sorption capability because raw SSB tends to adsorb cations rather than anions. , Accordingly, environmentally benign metals such as Mg, Al, Ca, Cu, and Fe have been impregnated into SS and produced modified SSB with more functional groups. ,, Impregnation with Ca/Mg produces SSBs with excellent P adsorption behaviors because of their various organic functional groups and the Ca/Mg-containing nanoparticles. These Ca/Mg-containing nanoparticles play significant roles in P adsorption via electrostatic attractions with the formation of Ca–P/Mg–P bonds. , Additionally, Ca/Mg-based chemicals can induce the inherent P in SS to form plant-bioavailable phosphates, such as hydroxyapatite …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To efficiently recover P from P extract, pretreatment of SS is necessary to produce SSB with a high P sorption capability because raw SSB tends to adsorb cations rather than anions. , Accordingly, environmentally benign metals such as Mg, Al, Ca, Cu, and Fe have been impregnated into SS and produced modified SSB with more functional groups. ,, Impregnation with Ca/Mg produces SSBs with excellent P adsorption behaviors because of their various organic functional groups and the Ca/Mg-containing nanoparticles. These Ca/Mg-containing nanoparticles play significant roles in P adsorption via electrostatic attractions with the formation of Ca–P/Mg–P bonds. , Additionally, Ca/Mg-based chemicals can induce the inherent P in SS to form plant-bioavailable phosphates, such as hydroxyapatite …”
Section: Introductionmentioning
confidence: 99%
“…5,25 Accordingly, environmentally benign metals such as Mg, Al, Ca, Cu, and Fe have been impregnated into SS and produced modified SSB with more functional groups. 24,26,27 Impregnation with Ca/Mg produces SSBs with excellent P adsorption behaviors because of their various organic functional groups and the Ca/Mg-containing nanoparticles. 28−30 These Ca/Mgcontaining nanoparticles play significant roles in P adsorption via electrostatic attractions with the formation of Ca−P/Mg−P bonds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Biochar with high porosity and plenty of liming and fertiliser-related elements (such as N, P and K) is preferred for improving soil properties [31]. A study conducted by [32] also indicated that the innate minerals of biomass could affect biochar properties significantly through interaction with its organic contents during pyrolysis process. However, removal of these intrinsic minerals before the pyrolysis process could significantly increase the optimum pyrolysis temperature (370 vs. 350 °C) required for the conversion of the biomass into biochar, as compared to untouched biomass.…”
Section: Biochar Elemental Compositionmentioning
confidence: 99%
“…However, removal of these intrinsic minerals before the pyrolysis process could significantly increase the optimum pyrolysis temperature (370 vs. 350 °C) required for the conversion of the biomass into biochar, as compared to untouched biomass. Interestingly, about 30.1% of C content of biomass could be secluded into biochar when there are no inherent biomass materials, simultaneously, lower amounts of low-molecular-weight organic compounds would be emitted during pyrolysis [32]. Therefore, the type and amount of minerals in biomass must be optimised according to the intended environmental application of biochar.…”
Section: Biochar Elemental Compositionmentioning
confidence: 99%
“…Nan et al. recently investigated the interaction of minerals in cow manure with biomass carbon along pyrolysis via TG-FTIR-MS . The gaseous products released from cow manure pyrolysis mainly included small molecules (such as acetic acid, butane, and so on), middle molecular compounds (such as furfural, furan, and pyrazole), and large molecular compounds (such as d -glucopyranoside, cortisol, cholestane, and so on).…”
Section: In Situ Characterization Of Biomass Pyrolysismentioning
confidence: 99%